2015
DOI: 10.1080/22201181.2015.1054617
|View full text |Cite
|
Sign up to set email alerts
|

The development of a scoring tool for the measurement of performance in managing hypotension and intra-operative cardiac arrest during spinal anaesthesia for caesarean section

Abstract: Consortium, Cleveland Clinic, Cleveland, OH, USA *Corresponding author, email: garth.horsten@gmail.com Background: At level one hospitals in South Africa a high annual number of maternal deaths occur due to the unrecognised/ untreated complications of spinal anaesthesia. The authors developed a clinical scenario and scoring system to measure intern performance in managing hypotension and cardiac arrest during spinal anaesthesia for caesarean section on a human patient simulator. This system was then subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…programmes. 10,13 To the best of our knowledge this is the first cross-sectional study of the perceptions and attitudes towards SBE in South Africa. Understanding SBE within the context of anaesthesia will allow for its further development and growth.…”
Section: Research and Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…programmes. 10,13 To the best of our knowledge this is the first cross-sectional study of the perceptions and attitudes towards SBE in South Africa. Understanding SBE within the context of anaesthesia will allow for its further development and growth.…”
Section: Research and Collaborationmentioning
confidence: 99%
“…6 Little is known about the current practices of SBE within South Africa, with limited published research relating to SBE in anaesthesia. 10 The objectives of this study were to describe: i) the state of SBE in anaesthesia within South Africa and a selection of other settings; ii) the learner groups targeted with SBE; iii) the tools used to assess performance during SBE events; iv) the learning objectives targeted; v) the evaluation of the quality and impact This survey aims to provide a greater understanding of the current state of SBE in South Africa, facilitating further collaboration, research and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate standardised tools should be developed to assess the performance of interns on common anaesthetic obstetric emergencies, such as those for the management of spinal hypotension and cardiac arrest. [26] We used elements of the DAS difficult obstetric airway algorithm as a basis for our study, where the assessed items were weighted in conjunction with local experts to yield the checklist assessment. There were strong correlations between the 2 assessors' checklist scores and their global ratings, thus supporting the reliability of the assessment data.…”
Section: Researchmentioning
confidence: 99%
“…Its use has become widespread in medical education, and a recent SA anaesthesia study has shown that it is feasible as an assessment tool in this country. [37] Implementing anaesthesia simulation training in SA has the potential to improve anaesthesia skills of interns, community service doctors and rural doctors.…”
Section: Priority 9 Studies Of the Efficacy Of Simulation Training Tmentioning
confidence: 99%